Clinical Applications of the Intercostal Artery Perforator Flap for Trunk Reconstruction - Young Jun Kim; Woo Young Choi; Ji Seon Cheon; Min Hyub Choi (Archives of Plastic Surgery, 2023)
Background Trunk defects can occur because of surgical site infections after spinal surgery, resection of malignant tumors, or trauma. Herein, we present our experience of using intercostal artery perforator (ICAP) flaps to reconstruct trunk defects without noteworthy complications. Fourteen patients underwent reconstruction with ICAP flaps between March 2015 and March 2019. Methods Patients' data, including age, sex, the cause of the defect, defect size, perforator location, flap size, complications, and follow-up period, were retrospectively reviewed. The mean age of the patients was 56.5 years (range, 19–80 years). All operations were performed after the results of bacterial culture from the wound showed no microbial growth. We found reliable perforators around the defect using Doppler ultrasonography. The perforator flaps were elevated with a pulsatile perforator and rotated in a propeller fashion to the defects. We performed five dorsal and two lateral ICAP flaps. The mean flap dimensions were 12 × 5.5 cm2 (range, 6 × 5 to 18 × 8 cm2). Results Primary closure of the donor site was performed. Marginal congestion was observed as a complication in one case, but it healed with no need for revision. The mean follow-up period was 8 months. All patients were satisfied with the surgical outcomes. Conclusion ICAP flaps can be easily mobilized, thereby reducing donor site morbidity without sacrificing the underlying muscles for trunk reconstruction. Therefore, these flaps are useful options for the reconstruction of trunk defects.